Strained Interpretations: the labour of imaging lesbian lifestyles in art - Bezuidenhout, Mandi-Anne (University of the Free State, 2017)
My hypothesis stems from my work in the studio, in three distinct media, namely photography, installation art and sculpture. I observe as an artist and member of the lesbian community, the difficulty of imaging and making lesbian lifestyles public. In each medium, my artwork intimately investigates this lesbian struggle from various angles. I experience that such lifestyles often entail either painful secrecy or the brash exposure or exhibition of these lifestyles in crude, exposed, shocking and activistic images. In my work I thematise the difficulty, effort and strain experienced by lesbians to be acknowledged in society through images. I investigate if the medium of the artwork can suggest difficulty and strain, and if this can initiate an inner dialogue with the spectator in order to draw attention to the lesbian subject matter he or she is witnessing. As a homosexual artist portraying a deeply controversial subject matter to an often conservative society/spectator: How can the struggle and difficulty in the process of making such visual art, be made evident or be anticipated, in the difficulty of the interpretation process when the work of art is received and revealed. Will the level of respect generated from the process of art making in various visual art media, about intimate moments experienced by lesbians in our society, be experienced by the spectator with the same amount of respect and acknowledgement? How do presentations or depictions of South African lesbian lifestyles differ from those in the rest of the world and why is it an ongoing struggle to expose these lifestyles in images without an overwhelming fear of rejection, judgment and ultimately exclusion? In order to answer these questions I investigate how the difficulty experienced by lesbians to be acknowledged in society can be suggested in images and how this has been done in past art. I analyse the works of Zanele Muholi and Jean Brundrit who are the leading South African contemporary artists currently representing lesbian visibility and exposure in this country. Artists from elsewhere such as Mary Coble and Sophia Wallace conceptually relate to my research, as they are both concerned with the deeper undertones of struggle and strife associated with acknowledgement of images of lesbian lifestyles. As opposed to their objectives to reveal difficult lesbian narratives through brash exposure and shock value, my objectives shift to research on the slowing down of the processes of interaction between artwork and spectator. I ask the question if the internalized melancholy which lesbians become subject to according to Judith Butler, in her book Gender Trouble (1999), could be translated into heaviness and processes of slowing down interpretation. Could the slowing down of the process of interpretation be implemented as a strategy to draw attention to the social difficulties experienced by lesbians? Could this slowing down of the interpretation process allow the spectator or participant inner contemplation and a suggestion of the experience of melancholy? Could the slowing down of the process of interpretation, on the other hand, inspire self-awareness in the participant/spectator to become a witness who is implicated? In which ways can the interpretation process by spectator or participant be slowed down? Does self-awareness about the interpretation process inspire an intensification of the experience of the subject matter – does it draw attention to the lesbian subject matter? Does this self-awareness aid in instigating a witness experience in the participant? How is a witness experience inspired in the participant or spectator? Can allusive gestures or subtle hints (photography), or the experience of physical weight (sculpture), or the inversion of pictures (installation of camera obscuras) contribute to this?
Dissertation (M.A. (Fine Arts))--University of the Free State, 2017
Keywords: Fine arts; History of arts; Gender; Sexuality